Exchange Rate Reconnect - Lilley, Andrew; Maggiori, Matteo; Neiman, Brent; Schreger, Jesse (The Review of Economics and Statistics, 2022)
It is surprisingly difficult to find economic variables that strongly comove with exchange rates, a phenomenon codified in a large literature as “exchange rate disconnect.” We demonstrate that a variety of common proxies for global risk appetite, which did not comove with exchange rates prior to 2007, have provided significant in-sample explanatory power for currencies since then. Furthermore, during the 2007–2012 period, U.S. purchases of foreign bonds were highly correlated with these risk measures and with exchange rates. Our results support the narrative that the U.S. dollar's role as an international and safe-haven currency has surged since the global financial crisis.